Pelatihan Teknologi Pemipih Purun sebagai Strategi Pemberdayaan Kelompok Usaha Pengrajin di Desa Tumbang Nusa: Training on Purun-Flattening Technology as a Strategy to Empower Artisan Business Groups in Tumbang Nusa Village - Saputra Adiwijaya; Siti Unvaresi Misonia Beladona; Fitriana Selvia; Meiyanti Ratna Kumalasari; Laila Zahra; Irvan Maulana Fiqih; Muhamad Arief Rafsanjani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Tumbang Nusa Village, Pulang Pisau Regency, Central Kalimantan, has natural resource potential in the form of purun (Lepironia articulata), which grows abundantly in peatlands, swamps, and along riverbanks. Purun has long been utilized by the local community as raw material for handicrafts such as mats, bags, wallets, and eco-friendly straws. However, the purun-flattening process, which is still carried out manually, creates several challenges, including lengthy production times, inconsistent fiber quality, and heavy physical burdens on artisans. This community service activity aimed to provide training on the use of purun-flattening technology for the "Nusa Sehati" Joint Business Group to improve efficiency, quality, and production capacity. The implementation method included a pre-test, socialization, training, practical tool use, and a post-test to measure the activity's effectiveness. A total of 20 participants were involved, the majority of whom were women of productive age. The results indicated significant improvements in ease of use, time efficiency, product quality, and fatigue reduction. In the pre-test, only 40% of participants found manual flattening easy; after using the tool, this increased to 95% in the post-test. All participants (100%) stated that the tool saved production time and reduced fatigue, while 90% rated the fiber quality as very good. Regarding acceptance, 85% of participants stated they would definitely continue using the tool. Thus, training in the application of purun-flattening technology proved effective in enhancing artisans' skills, productivity, and competitiveness. This activity also contributes to strengthening the local economy by leveraging regional potential in a sustainable, environmentally friendly manner.